Grayscale Lithography and a Brief Introduction to Other Widely Used Lithographic Methods: A State-of-the-Art Review - Svetlana N. Khonina; Nikolay L. Kazanskiy; Muhammad A. Butt (Micromachines)
Lithography serves as a fundamental process in the realms of microfabrication and nanotechnology, facilitating the transfer of intricate patterns onto a substrate, typically in the form of a wafer or a flat surface. Grayscale lithography (GSL) is highly valued in precision manufacturing and research endeavors because of its unique capacity to create intricate and customizable patterns with varying depths and intensities. Unlike traditional binary lithography, which produces discrete on/off features, GSL offers a spectrum of exposure levels. This enables the production of complex microstructures, diffractive optical elements, 3D micro-optics, and other nanoscale designs with smooth gradients and intricate surface profiles. GSL plays a crucial role in sectors such as microelectronics, micro-optics, MEMS/NEMS manufacturing, and photonics, where precise control over feature depth, shape, and intensity is critical for achieving advanced functionality. Its versatility and capacity to generate tailored structures make GSL an indispensable tool in various cutting-edge applications. This review will delve into several lithographic techniques, with a particular emphasis on masked and maskless GSL methods. As these technologies continue to evolve, the future of 3D micro- and nanostructure manufacturing will undoubtedly assume even greater significance in various applications.